2018
DOI: 10.1002/jcph.1067
|View full text |Cite
|
Sign up to set email alerts
|

No Increased Risk of Fracture in Patients Receiving Antimuscarinics for Overactive Bladder Syndrome: A Retrospective Cohort Study

Abstract: To date, the actual relationship between antimuscarinics for overactive bladder (OAB) syndrome and the subsequent risk of a fracture remains unclear. The aim of this retrospective cohort study was to demonstrate the association between antimuscarinics for OAB and fractures using a large population-based data set. Data used in this study were taken from the Taiwan Longitudinal Health Insurance Database 2005. We identified 2927 OAB patients who received antimuscarinics as the study cohort and 11 708 matched OAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…One study by Gomes et al reported that the risk of serious falls among individuals with OAB treated with two different antimuscarinics was similar (0.8% for tolterodine vs. 0.7% for oxybutynin) [ 20 ]. In the other study, the unadjusted PAR for any fracture was slightly higher among individuals with OAB who had been prescribed an antimuscarinic (3.01) compared to those who had not been prescribed an antimuscarinic (2.77) [ 28 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study by Gomes et al reported that the risk of serious falls among individuals with OAB treated with two different antimuscarinics was similar (0.8% for tolterodine vs. 0.7% for oxybutynin) [ 20 ]. In the other study, the unadjusted PAR for any fracture was slightly higher among individuals with OAB who had been prescribed an antimuscarinic (3.01) compared to those who had not been prescribed an antimuscarinic (2.77) [ 28 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…4 ) [ 8 , 22 , 27 ]. No difference in risk of fractures was observed in either study that examined the impact of treatment [ 20 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous patients with bladder diseases may exhibit a complex of symptoms known as overactive bladder (OAB), characterized by urgency, frequency and nocturia, with or without urinary incontinence ( 4 ). It was reported that metastatic breast cancer was also associated with OAB-like symptoms ( 4 , 5 ). Whether these symptoms are associated with molecular features or with prognosis of bladder cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Antagonists of muscarinic acetylcholine receptors (mAChRs) remain the first-line therapy for treating OAB symptoms, such as urgency ( 6 ). Understanding the role of mAChRs in OAB requires the examination of all five receptor subtypes (M1R-M5R), all of which being located in the urothelium ( 4 ). The urothelium could respond to muscarinic agonist stimulation by self-releasing acetylcholine (ACh), which may modulate afferent activity in turn ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 32 34 ] The study used the Longitudinal Health Insurance Database (LHID) obtained from the NHI Research Database (NHIRD), consisting of 1 million beneficiaries randomly sampled from the original NHI beneficiaries. [ 35 , 36 ] The National Health Research Institute in Taiwan permitted the access to the data in the NHIRD and the database includes the entire registry and claims data from this this health insurance system. [ 32 37 ] The accuracy of diagnosis in the NIRD has been validated for several diseases, including stroke and CKD.…”
Section: Methodsmentioning
confidence: 99%